2018
DOI: 10.1111/jne.12548
|View full text |Cite
|
Sign up to set email alerts
|

Steroids, stress and the gut microbiome‐brain axis

Abstract: It is becoming well established that the gut microbiome has a profound impact on human health and disease. In this review, we explore how steroids can influence the gut microbiota and, in turn, how the gut microbiota can influence hormone levels.Within the context of the gut microbiome-brain axis, we discuss how perturbations in the gut microbiota can alter the stress axis and behaviour. In addition, human studies on the possible role of gut microbiota in depression and anxiety are examined. Finally, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 119 publications
(236 reference statements)
0
109
0
1
Order By: Relevance
“…109,110 Therefore, real or perceived stress can modulate this bidirectional communication in a way that increases dysbiosis and increases an individual’s propensity to develop disease. 111,112 For example, stress can trigger the flight or fight response, increasing the production of corticotropin-releasing-hormone and catecholamine production from the central nervous system (CNS) which then modulates gut microbiome function. 112,113 On the other hand, bottom up processes involving release of microbial products such as tryptophan or serotonin during stressful events can contribute to the enteric dysbiosis, increased intestinal permeability and the release of certain neurotransmitters associated with certain diseases.…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…109,110 Therefore, real or perceived stress can modulate this bidirectional communication in a way that increases dysbiosis and increases an individual’s propensity to develop disease. 111,112 For example, stress can trigger the flight or fight response, increasing the production of corticotropin-releasing-hormone and catecholamine production from the central nervous system (CNS) which then modulates gut microbiome function. 112,113 On the other hand, bottom up processes involving release of microbial products such as tryptophan or serotonin during stressful events can contribute to the enteric dysbiosis, increased intestinal permeability and the release of certain neurotransmitters associated with certain diseases.…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…Prior work in the field of metagenomics has emphasized the role of microbiome stability on host physiology (Lozupone et al, 2012;Faith et al, 2013;Mehta et al, 2018;Tetel et al, 2018). What we found in this study was that phylogenetic assembly of longitudinal participant data by microbiome state may be an option to identify participants experiencing microbiome disruption events.…”
Section: Microbiome Stability and The Regulation Of Stress Perceptionmentioning
confidence: 64%
“…What we found in this study was that phylogenetic assembly of longitudinal participant data by microbiome state may be an option to identify participants experiencing microbiome disruption events. There are two proposed mechanisms of how microbiome function may be a feature of stress resilience, in which the microbiome may act through bottom up or top down effects contributing to the observed stress phenotype (Foster et al, 2017;Tetel et al, 2018). In the top down hypothesis, the physiologic effects of stress changes the innervation of the gastrointestinal system, leading to a new physiological state and ultimately to novel niche selection within the gut lumen (Kelly et al, 2015).…”
Section: Microbiome Stability and The Regulation Of Stress Perceptionmentioning
confidence: 99%
“…Recent research has revealed the diverse influence of microbiota and their metabolites on many aspects of host health and fitness, including digestion and nutrient uptake, metabolism and immune development (Hooper et al 2012; Rea et al 2016). In mammals, stress is well known to disrupt the diversity, structure and function of the microbiome which, in turn, has been associated with long term health effects in the host, including metabolic and immune impairment, and a range of diseases (Foster et al 2017; Tetel et al 2018). The mechanisms by which stress impacts the microbiome are complex, and not fully understood.…”
Section: Introductionmentioning
confidence: 99%